(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
This paper proposes to study briefly the background, the development, and the consequences of the struggle of Cordoba in 1918. To keep in-depth breakdowns produced in the field of education and culture in Argentina, we are interested in a dialectic understanding of the interrelationships among intellectuals, university and changes in the various moments of political history. Social and political processes affect the dynamics of transformation of institutions. Therefore, it is pertinent their analysis and interpretation. Disputes between tradition and reform in the educational system will be a constant, particularly in the university. It is for that reason that we will try to see the major challenges in the university system in Argentina recently, and the validity of the utopia of university reform in the context of Latin American integration scenarios.